GSTA1 gene polymorphisms are associated with cyclophosphamide effectiveness in lupus nephritis patients: A case-control study in Indonesia - Indrawijaya, Yen YA.; Artarini, Aluicia A.; Hamijoyo, Laniyati; Iwo, Maria I. (Narra Sains Indonesia, 2024)
Glutathione-S-transferase alpha-1 (GSTA1) is an enzyme with high conjugation activity against aldophosphamide, a metabolite of cyclophosphamide and promoter polymorphisms in GSTA1 may influence the cyclophosphamide effectiveness. The aim of this study was to evaluate the effectiveness and side effects of cyclophosphamide in lupus nephritis patients, using GSTA1 variants as predictors. A case-control study was conducted at Hasan Sadikin Hospital, Bandung, Indonesia, involving 100 lupus nephritis patients from February 2023 to January 2024. The PCR-Sanger sequencing was used to genotype five selected single nucleotide polymorphisms (SNPs) in the GSTA1 promoter: -52 A>G, -69 T>C, -513 A>G, -567 G>T, and -631 G>T. The endpoint was assessed after six doses of cyclophosphamide by evaluating renal function, disease activity and side effects. Results indicated that six doses of intravenous cyclophosphamide treatment improved renal function and disease activity in the patients, as evidenced by significant changes in serum creatinine (0.79 vs 0.69 mg/dL), dipstick proteinuria (3.00 vs 1.50), creatinine clearance (98.50 vs 109.50 mL/min), and Modified Systemic Lupus Erythematosus Disease Activity Index 2000 (M-SLEDAI-2K) score (8.61 vs 6.95). The AG genotype at -513 A>G was associated with reduced cyclophosphamide effectiveness (odds ratio (OR): 0.19; 95%CI: 0.19–0.60; p=0.019). The GT genotype at -631 G>T independently increased the progression of anemia (OR: 2.41; 95%CI: 0.26–22.12; p=0.040). This study highlights that the presence of GSTA1 variants affected cyclophosphamide effectiveness in lupus nephritis patients, with heterozygous polymorphisms at -513 (AA to AG) and -631 (TT to GT) predicting reduced effectiveness of cyclophosphamide by enhancing GSTA1 promoter activity, while anemia further exacerbated lupus nephritis disease severity. GSTA1 polymorphism was not associated with the presence of alopecia, amenorrhea, gastrointestinal disorders, and leukopenia during cyclophosphamide therapy.